Species-Specific Differences in Sperm Chromatin Decondensation Between Eutherian Mammals Underlie Distinct Lysis Requirements - Ribas-Maynou, Jordi; Garcia-Bonavila, Estela; Hidalgo, Carlos O.; Catalán, Jaime; Miró, Jordi; Yeste, Marc (Frontiers in Cell and Developmental Biology, 2021)
Sperm present a highly particular DNA condensation that is acquired during their differentiation. Protamines are key elements for DNA condensation. However, whereas the presence of protamine 1 (P1) is conserved across mammalian species, that of protamine 2 (P2) has evolved differentially, existing only few species that use both protamines for sperm DNA condensation. In addition, altered P1/P2 ratios and alterations in the expression of P1 have previously been associated to infertility and DNA damage disorders. On the other hand, different methods evaluating DNA integrity, such as Sperm Chromatin Dispersion (SCD) and Comet tests, need a previous complete DNA decondensation to properly assess DNA breaks. Related with this, the present study aims to analyze the resilience of sperm DNA to decodensation in different eutherian mammals. Sperm samples from humans, horses, cattle, pigs and donkeys were used. Samples were embedded in low melting point agarose and treated with lysis solutions to induce DNA decondensation and formation of sperm haloes. The treatment consisted of three steps: (1) incubation in SDS + DTT for 30 min; (2) incubation in DTT + NaCl for 30 min; and (3) incubation in DTT + NaCl with or without proteinase K for a variable time of 0, 30, or 180 min. How incubation with the third lysis solution (with or without proteinase K) for 0, 30, and 180 min affected DNA decondensation was tested through analyzing core and halo diameters in 50 sperm per sample. Halo/core length ratio was used as an indicator of complete chromatin decondensation. While incubation time with the third lysis solution had no impact on halo/core length ratios in species having P1 and P2 (human, equine and donkey), DNA decondensation of pig and cattle sperm, which only present P1, significantly (P < 0.05) increased following incubation with the third lysis solution for 180 min. In addition, the inclusion of proteinase K was found to accelerate DNA decondensation. In conclusion, longer incubations in lysis solution including proteinase K lead to higher DNA decondensation in porcine and bovine sperm. This suggests that tests intended to analyze DNA damage, such as halo or Comet assays, require complete chromatin deprotamination to achieve high sensitivity in the detection of DNA breaks.